Sobre los caminos de la paz en Colombia y las manos que los surcan: Reseña de “As war ends. What Colombia Can Tell Us About the Sustainability of Peace and Transitional Justice” - Sierra Rivera, Cindy Marcela (Ciudad Paz-ando, 2023)
Reseña de: Meernik, J., DeMeritt, J. y Uribe-López, M. (Eds.). (2019). As War Ends: What Colombia Can Tell Us About the Sustainability of Peace and Transitional Justice. Cambridge: Cambridge University Press. https://doi.org/10.1017/9781108614856